Reinforcement of clean farming by using poultry manure and dry yeast and its effects on the growth and productivity of lettuce (Lactuca sativa L.) - Ismail, Mukhalad. H.; Al-Asadi, Zainab Noori (Journal of Kerbala for Agricultural Sciences, 2023)
A field study was carried out during the growing season 2020 in one of the private field in Sufia area / Ramadi district in order to determine the best combination of adding poultry manure and spraying with dry yeast on the growth and yield of lettuce plant (Lactuca sativa L.) Polaris cultivar. The study included the addition of poultry manure and dry yeast spraying, where a combination of treatments was made as follows: 1- the control treatment 2- 10% poultry Manure3- 15% poultry Manure4- Three grams dry yeast per liter for the experimental unit 5- Six grams dry yeast per liter for the experimental unit 6- 10 % poultry manure + 3 gm per liter dry yeast 7- 10% poultry manure + 6 gm dry yeast per liter 8 - 15% poultry manure + 3 gm dry yeast per liter 9- 15% poultry manure + 6 gm dry yeast per liter. The experiment was carried out according to a randomized complete block design with three replications, and treatments means were compared according to the L.S.D test at a significant level of 5%. The results showed that the combination (15% poultry Manure+ 6 g L-1 of dry yeast) was significantly outperformed of the following characteristics: head height, number of leaves, average head weight, leaf area, percentage of nitrogen in the leaves, with 42.69 cm, 70.493 leaves plant-1, 1.860 kg, 1451.33 cm2, and 3.15%, respectively. The combination (10% poultry Manure+ 6 g L-1of dry yeast) outperformed in percentage of carbohydrates (40.80%). It is concluded from this study that these fertilizers were characterized by giving positive results in vegetative growth characters, leaf content of nutrients and productivity.